2006
DOI: 10.1021/jf0624300
|View full text |Cite
|
Sign up to set email alerts
|

Model Studies on Acrylamide Generation from Glucose/Asparagine in Aqueous Glycerol

Abstract: Acrylamide formation from asparagine and glucose in different ratios in neutral glycerol/water mixtures was found to increase with decreasing water activity (0.33 < or = aw < or = 0.71 investigated) and increasing temperature (120 degrees C < or = T < or = 160 degrees C investigated). The initial rate of acrylamide formation was found to be approximately proportional to the asparagine concentration for an excess of asparagine, but less dependent on an excess of glucose. A steady-state concentration of acrylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Moreover, it is hard to indentify the effect of initial water activity when working in a small a w range (De Vleeschouwer et al 2008, Robert et al 2004, the use here of larger initial water activity range allowed to overcome this difficulty. The increase of the initial formation rate with increasing temperature and decreasing initial water activity was already highlighted in aqueous glycerol asparagine-glucose model system (mobility does not, depend on water content), within an initial water activity range varying from 0.33 to 0.71 (Hedegaard et al 2007). The authors suggested that in higher a w the elimination of water molecule during Schiff base formation was the rate determining step, whereas in lower a w , Schiff base decarboxylation was the rate-determining one.…”
Section: Effect Of Initial Water Activity On Acrylamide Formation/elimentioning
confidence: 68%
See 2 more Smart Citations
“…Moreover, it is hard to indentify the effect of initial water activity when working in a small a w range (De Vleeschouwer et al 2008, Robert et al 2004, the use here of larger initial water activity range allowed to overcome this difficulty. The increase of the initial formation rate with increasing temperature and decreasing initial water activity was already highlighted in aqueous glycerol asparagine-glucose model system (mobility does not, depend on water content), within an initial water activity range varying from 0.33 to 0.71 (Hedegaard et al 2007). The authors suggested that in higher a w the elimination of water molecule during Schiff base formation was the rate determining step, whereas in lower a w , Schiff base decarboxylation was the rate-determining one.…”
Section: Effect Of Initial Water Activity On Acrylamide Formation/elimentioning
confidence: 68%
“…Very slight promoting effect of water activity on acrylamide amount was found in an asparagine-glucose model system (De Vleeschouwer et al 2007, De Vleeschouwer, van der Plancken, van Loey, & Hendrickx 2008. The opposite trend was found in aqueous glycerol asparagine model system, revealing a decrease in acrylamide formation with increasing water activity (Hedegaard et al 2007). The same tendency was observed in real food (cake) where acrylamide formation did not occur in a large extent when moisture content was higher than 5% (Elmore et al 2005).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Single-response models based on empirical overall reaction kinetics have been extensively used. Acrylamide formation has been thus modeled as a first order reaction (Gökmen & Senyuva, 2006a;Hedegaard, Frandsen, Granby, Apostolopoulou, & Skibsted, 2007), as a pseudo-first order reaction (Amrein, Limacher, Amadò, & Escher, 2006) or as a second order reaction (De Vleeschouwer, Van der Plancken, Van Loey, & Hendrickx, 2006) according to reaction conditions and reactant concentrations. Acrylamide elimination has been usually modeled as a first order kinetics (Biedermann, Biedermann-Brem, Noti, & Grob, 2002;Gökmen & Senyuva, 2006a).…”
Section: Mitigation Optionsmentioning
confidence: 99%
“…Acrylamide formation is affected by many factors, such as precursors (i.e., reducing sugar and asparagine) concentration, pH, water content and activity, physical state of the food, and process parameters, mainly represented by the heating time and temperature [12, 28,48,57,60,62,69,70,77]. For instance, acrylamide formation is favored by a high heating temperature and time, as well as pH values, a relatively low water content and activity.…”
Section: Introductionmentioning
confidence: 99%